THE ADAPTATION OF THE ARMENIAN VERSION OF THE STUDENT'S PSYCHOLOGICAL WELL-BEING SCALE - Asriyan, Elina; Karapetyan, Nare; Samokhvalova, Anna (Modern Psychology, 2022)
The article is devoted to the choice of tools for assessing the psychological well-being of students and the description of the process of adapting the appropriate methodology. The paper discusses the conceptual foundations of the study of the phenomenon of well-being, theoretical approaches and research data of Armenian and foreign authors. The experimental section presents the stages of choosing instruments for studying psychological well-being, the features of choosing methods and their adaptation. The analysis of the study data revealed the characteristic features of the indicator in question among Armenian and Russian students, based on the results obtained, the choice of tools and the corresponding stages of validation were substantiated. The research stages were analyzed taking into account the war and post-war problems on the Armenian and Russian sides. A number of distinguishing features are presented, which were changed in other stages of research due to the Russian war.
Keywords: stress factors; stress; psychological well-being; mental health; subjective well-being; validity; adaptation; war; pandemic